Synthesis And Anti-Fungal Activity of N'-(3-Bromophenyl)-2-{[5-(4-Methylpyridine-3-Yl)-1,3,4-Oxadiazol-2-Yl] Sulfanyl} Acetohydrazides Derivatives - Teli, Dharyappa; Metre, Anil; Teli, Sangappa; Kotnal, R B (Asian Journal of Pharmaceutical Research and Development, 2023)
A series of Pyridine derivatives were prepared and evaluated for, antibacterial and antifungal activities. The title compounds were prepared by condensation of substituted aromatic aldehydes with N'-(3-bromophenyl)-2-{[5-(4-methylpyridine-3-yl)-1,3,4-oxadiazol-2-yl] sulfanyl} acetohydrazides. The structures of all these compounds were confirmed by their spectral studies. Among synthesized compounds (DK-IB, DK-IC, DK-IG, and DK-IH) have shown good anti-fungal activity and Anti-Microbial Activity (500 µg mL-1) when compared to reference drugs Ketoconazole (25µg mL-1) and Chloramphenicol (25 µg mL-1). In this study, few derivatives showed a broad spectrum of antimicrobial activity at low concentrations. The MICs (Minimum inhibitory concentration) of some compounds are 8-16µg mL-1.